On the buffer capacity of CO2-charged seawater used for carbonation and subsequent mineral sequestration - Wolff-Boenisch, Domenik (Elsevier BV, 2011)
Successful mineral trapping of carbon dioxide faces the challenge of effectively titrating a CO2-charged acidic injection solution to pH conditions favorable to carbonate precipitation -using the rock as primary alkalinity source. To illustrate the magnitude of this task, buffer capacities of seawater solutions equilibrated with different partial pressure of CO2 are presented, under open and closed conditions. A number of mechanisms can be evoked to overcome the large buffer intensity of the injection fluid, including dilution, dissolution kinetic catalysis and increasing reaction temperature. Buffer capacity – pH plots are presented to aid in understanding how buffer capacity changes as a function of the presence and concentration of key solutes, like fluoride.